Manajemen Pendidikan Pesantren Ketrampilan - Maratush Sholikhah (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2017)
Islamic boarding schools generally carry out the mandate to be able to provide moral education based on the Shari'a. Today's modern era with various technological advances that result must be prepared to face the challenges of the world both in terms of intellectual, especially in terms of economic or skills. When in pesantren education is only focused on intellectual education without providing a container of knowledge about skills, the influence gained by them seekers of knowledge in pesantren will find it difficult to face the modern challenges that exist today. Therefore, what is the strategy of pesantren from all existing elements, to improve by looking at the challenges that will be faced by students in the pesantren. The pesantren management will automatically control all the planned programs without reducing or overloading which results in a pure image of the pesantren sinking. In this case there are several pesantren which can be a mirror to create programs that lead to the improvement of the skills of the students. the pesantren in question is the Miftahul Mubtadiin male boarding school and the Rahmatal Lil 'Alamin Islamic Boarding School located in Nganjuk Regency. Both pesantren have different programs but on the same goal, namely to equip students in the field of skills. The skills referred to here are printing, raising livestock, gardening, farming, building, making calendars, sewing and so on.